Impact of the COVID-19 pandemic and related control measures on cancer diagnosis in Catalonia: a time-series analysis of primary care electronic health records covering about five million people. Issue 5 (18th May 2021) - Coma, Ermengol; Guiriguet, Carolina; Mora, Nuria; Marzo-Castillejo, Mercè; Benítez, Mencia; Méndez-Boo, Leonardo; Fina, Francesc; Fàbregas, Mireia; Mercadé, Albert; Medina, Manuel
Abstract : Objective: Cancer care has been disrupted by the response of health systems to the COVID-19 pandemic, especially during lockdowns. The objective of our study is to evaluate the impact of the pandemic on the incidence of cancer diagnoses in primary care. Design: Time-series study of malignant neoplasms and diagnostic procedures, using data from the primary care electronic health records from January 2014 to September 2020. Setting: Primary care, Catalonia, Spain. Participants: People older than 14 years and assigned in one of the primary care practices of the Catalan Institute of Health with a new diagnosis of malignant neoplasm. Main outcome measures: We obtained the monthly expected incidence of malignant neoplasms using a temporary regression, where the response variable was the incidence of cancer from 2014 to 2018 and the adjustment variables were the trend and seasonality of the time series. Excess or lack of malignant neoplasms was defined as the number of observed minus expected cases, globally and stratified by sex, age, type of cancer and socioeconomic status. Results: Between March and September 2020 we observed 8766 (95% CI 4135 to 13 397) fewer malignant neoplasm diagnoses, representing a reduction of 34% (95% CI 19.5% to 44.1%) compared with the expected. This underdiagnosis was greater in individuals aged older than 64 years, men and in some types of cancers (skin, colorectal, prostate). Although the reduction was predominantly focused during the lockdown, expected figures have not yet been reached (40.5% reduction during the lockdown and 24.3% reduction after that). Conclusions: Reduction in cancer incidence has been observed during and after the lockdown. Urgent policy interventions are necessary to mitigate the indirect effects of the COVID-19 pandemic and related control measures on other diseases and some strategies must be designed in order to reduce the underdiagnosis of cancer.